Human papillomavirus 16 E6 oncoprotein promotes up-regulation of RNA-binding protein Sam68 in head and neck cancer - Cerasuolo, Andrea; Pecchillo Cimmino, Tiziana; Gagliarde, Salvatore; D’Orsi, Petra Claudia Camilla; Starita, Noemy; Amiranda, Sara; Tornesello, Anna Lucia; Dassi, Luisa; Bonelli, Patrizia; Tuccillo, Franca Maria; Buonaguro, Franco Maria; Longo, Francesco; et al. (Frontiers in Microbiology, 2026)
Head and neck squamous cell carcinoma (HNSCC) are a heterogeneous group of tumors linked to diverse risk factors, such as tobacco and alcohol use, as well as human papillomavirus (HPV) infection. HPV16 E6 and E7 oncoproteins are the main players of cell transformation, with the E6*I isoform increasing during neoplastic progression. The aim of this study was to evaluate the role of cellular splicing factors in the production of E6*I in HPV16-related HNSCC. We have evaluated the levels of splicing factors mRNA (HNRNPA1, HNRNPA2B1, SRSF1, SRSF2, SRSF3, BRM and SAM68) as well as HPV16 E6 and E6*I mRNAs by qPCR in HNSCC as well as in SCC152 and SCC154 cell lines. Overall, 42.4% of HNSCC tested positive for HPV16 DNA, and among these 54% expressed E6*I mRNA. The SRSF3, BRM and SAM68 transcripts were significantly higher in HPV-positive compared to HPV-negative HNSCC (p < 0.05), and SAM68 with HPV16 E6*I transcripts concordantly high in both HNSCC and cell lines (r = 0.7). Transduction of LXSN_E6 in HPV-negative PCA5 cell line induced production of E6*I mRNA and overexpression of Sam68 protein. In addition, silencing of SAM68 in SCC152 caused decrease of E6*I RNA and reduced cell growth at 48 hr after siRNA transfection. Higher expression of splicing factors in association with HPV was also confirmed in HNSCC TCGA dataset. In conclusion, our results suggest an interplay between the splicing machinery and HPV16 E6*I in HNSCC. These new observations are crucial for the development of novel therapeutic strategies based on SAM68 inhibitors.